Internet Addiction Among Iranian Students of Medical Sciences - Molook Torabi; Arash Shahravan; Atefeh Bahabin; Iman Mohammadzadeh; Marzieh Karimi Afshar (Association of Support to Oral Health Research (APESB), 2022)
Objective: To identify the prevalence of Internet addiction (IA) and associated factors among Iranian medical students. Material and Methods: The cross-sectional survey was conducted on a random sample of 400 students. The self-administered questionnaire consisted of two sections: the first section was sociodemographic data, data about student's relations, and Internet use characteristics; the second part aimed at assessment of the level of IA using Young's 20-item scale for IA. Data analyzed in SPSS 20 at 0.05 significant level. Results: Considering their familiarity with the Internet, 80.3% stated personal experience and 12.3% individuals stated educational periods held outside the university. The most locations of using the Internet were dormitories (21.0%) and houses (43.5%). Concerning hours of Internet use, 45.2% used the Internet more than two hours per day. One hundred sixty-eight individuals (42.0%) stated that they used the Internet less than 15% for university activities. One hundred eighty-eight individuals (47.0%) used VPN and 75.5% were dissatisfied with Internet speed 61.2%. A total of 64.3% had a poor dependency on the Internet and the prevalence of IA was 3.5%. The mean score of IA questionnaire was 43.98 ± 15.92 from 125. The mean score of IA was higher in the male sex, but there was no significant correlation between sex and IA (p>0.05). There was not a significant correlation between the field of study and the year of entrance. Conclusion: The prevalence of Internet addiction among medical students was low. Identification of factors associated with IA can help in the planning of preventive programs to raise students' knowledge about the hazards IA.